Representasi Feminisme dalam Serial Gadis Kretek: Analisis Wacana Kritis Sara Mills - Medianasari Ferdianyta; Chatarina Heny Dwi Surwati (Universitas Sebelas Maret (UNS), 2024)
Film as a mass communication media conveys messages to the audience through audio-visual presentation. Filmmaking is driven by various social problems that occur in society, one of which is feminism. Feminism is a movement to fight for equal rights for women and men, as well as efforts to fight various forms of subordination against women. The persistence of gender equality issues in society, where injustice is often ignored and normalized, is the background to the importance of this research. This encourages researchers to examine the representation of feminism in film and identify the message of feminism contained in the Gadis Kretek series. The method used in this research is qualitative with Sara Mills's critical discourse analysis model, which highlights the position of the subject, object, and audience in understanding the message of feminism conveyed. The results show that Gadis Kretek series represents feminism through the main character, Dasiyah, referring to the classification of the concept of second wave feminism. There are 11 corpus that represent feminism in the series, such as women's struggle in a patriarchal social and cultural context, men's involvement in supporting feminism, and women's empowerment in facing multiple roles.